Identification of Weeds in Cassava Fields (Manihot Esculenta Crantz) in Glugur Rimbun, Sampecita Village, Kutalimbaru District - Suryani Sajar (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
The cassava cultivation agricultural sector in North Sumatra is vulnerable to attacks by plant pests, resulting in a decrease in production. One of the pests that are directly related to cassava cultivation is weeds with all their types, impacts, and biology. Therefore, identification measures are needed. This research aims to identify weed diversity by knowing the weed species and dominant weed species. Research on identifying weeds in cassava (Manihot esculenta Crantz) in Glugur Rimbun, Sampecita Village, Kutalimbaru District, Deli Serdang Regency aims to determine the types of weeds, density, dominance index, and species diversity index. This research was conducted from June to August 2023 using qualitative and quantitative methods. Weed sampling used a random quadrat method, 50 samples with a plot size of 2 m x 2 m. The results of the analysis of weed vegetation on cassava cultivation land in Glugur Rimbun showed that there were 10 types of weeds from 5 families, namely the types of weeds included in the broad-leaf weed group, there were 5 species, namely Asystasia gangeticum, Amaranthus spinosus, Ageratum conyzoides, Chromolaena odorata, Mimosa pudica. Other types of weeds that were found were grass weeds, namely Axonopus compressus, Eleusin indica, Ottochloa nodosa, Cynodon dactilon, Paspalum conjugatum. The types of weeds that dominate the Glugur Rimbun cassava fields are Eleusin indica (SDR 20.88%), Cynodon dactilon (SDR 17.96%), Asystasia gingaticum (SDR 14.06%), Ottochloa nodosa (SDR 13.90%).